(untitled) (Janaki Medical College Journal of Medical Science, 2022)
Background and Objectives: The practice of blood donation is largely dependent on one’s level of education and attitude. Over 13 thousand blood facilities in 169 countries report collecting 106 million blood donations worldwide, totaling 118.5 million. However, there is still no equilibrium between blood demand and supply. Every year, in underdeveloped nations like Nepal, the need for safe blood is vital. Thus, this research was carried out to examine knowledge, practice, and attitude of blood donation among bachelor level Students. Material and Methods: This study used a systematic approach to analyze knowledge, attitudes, and practices towards blood donation among undergraduate students. A descriptive cross-sectional analysis was conducted utilizing stratified random samples on 110 samples. The pretest self-administered questionnaire was employed, which included both structured and semi-structured questions (r=0.70). The respondents included first- and second-year Bachelor of Social Work and Business Studies students, as well as first-year Bachelor of Computer Administration students. The data was analyzed using descriptive and inferential statistics (i.e., chi-square and spearman’s test) in SPSS 16 version. Results: This study found that 4.5% of the respondents had good knowledge, 63.7% had average knowledge, and 31.2% had poor knowledge. Among the respondents 23.60% had practice of blood donation while 76.10 % have not performed blood donation. The study also revealed 21.10% have negative attitude and 78.20% have positive attitude. There is a positive relationship between knowledge and attitude as Spearman’s coefficient value r = 0.150, and p= 0.117 (p>0.05) Conclusion: The study concludes the highest number of female respondents and a Hindu majority. Despite having a positive attitude, they have not practiced blood donation indicating a need to increase reinforcement and motivation among youths to bring positive changes in blood donation.